Examining the Process of Youth Influence by Sports Influencers on Online Media - Bagheri, Hamid; Abdavi, Fatemeh; Khodadadi, Mohammad Rasool (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aims to examine the processes through which sports influencers on online media impact the behavior, attitudes, and social dynamics of youth. Methods and Materials: This qualitative research was conducted in Tabriz, involving semi-structured interviews with 14 academic experts in the fields of media, sports, and youth studies. The participants were purposively selected to provide in-depth perspectives on the influence of sports influencers. The interviews were transcribed verbatim and analyzed using thematic analysis to identify key patterns and themes related to the influence processes of sports influencers. Findings: The study identified several key processes through which sports influencers impact youth. These include inspiring continuous activity, enhancing sports performance, modeling positive behavior and thinking, promoting social communication and networking, and contributing to technological and cognitive developments. Influencers inspire youth by sharing motivational stories and practical techniques, improve performance through educational content, model ethical behaviors and resilience, facilitate social connections within sports communities, and advance youth understanding of technology and media. Conclusion: Sports influencers play a significant role in shaping the behaviors, attitudes, and social interactions of youth. Their impact is multifaceted, promoting physical activity, skill development, ethical behavior, and social engagement. However, the influence of these influencers also poses risks that require careful management. Future research should explore strategies to leverage the positive aspects of influencer impact while mitigating potential harms. Practical initiatives should focus on educating influencers, supporting their roles, and guiding youth interactions with online media to maximize the benefits of sports influence in the digital age.